Optimasi Proses Produksi Biodiesel Dari Sawit Off Grade Menggunakan Katalis Zeolit Alam Teraktivasi Pada Tahap Transesterifikasi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Oil-palm off grade is a source of vegetable oil that unmaximum utilization from the rest of the sorting in Crude Palm Oil (CPO) factory. The availability of oilpalm off grade is about 7-10% of a CPO factory with capacity of 30 tons per hour. This research aims to produce biodiesel from oil-palm off grade with twostage reaction (esterification and transesterification) using activated natural zeolite catalysts in transesterification reaction. The other aims of this research is to study the influence of the reaction temperature (50, 60, 70°C), the molar ratio methanol : oil (6:1, 8:1, 10:1), and catalyst concentration (1, 3, 5%-wt) to yield of biodiesel and also to predict the optimum of proccess condition that give maximum yield. Natural zeolite is modificated by impregnation with 75% KOHsolution and calcined at 450°C for 4 hours. Response Surface Methodology (RSM) is used to know the influence of proccess condition which experiment design follows Central Composite Design (CCD) model with three variables. The highest yield of biodiesel is 92,04% at the reaction temperature of 60°C, themolar ratio of methanol : oil 8:1, and 3%-wt catalyst concentration. The variation of catalyst concentration gives significant effect to yield of biodiesel. The highercatalyst concentration will decrease yield of biodiesel. The prediction for optimum yield of biodiesel is 93,92% at the reaction temperature of 50,8°C, the molar ratio of methanol : oil 6,1:1, and 2,2%-wt catalyst concentration.Keywords : oil-palm off grade, biodiesel, natural zeolite modificated, response surface methodology, transesterification